2021
DOI: 10.1097/sla.0000000000004930
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy Followed by Active Surveillance Versus Standard Esophagectomy for Esophageal Cancer

Abstract: Objective: To compare overall survival of patients with a cCR undergoing active surveillance versus standard esophagectomy. Summary of Background Data: One-third of patients with esophageal cancer have a pathologically complete response in the resection specimen after neoadjuvant chemoradiotherapy. Active surveillance may be of benefit in patients with cCR, determined with diagnostics during response evaluations after chemoradiotherapy. Methods: A systematic review and meta-analysis was performed comparing ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…Can esophageal cancer learn from the “watch and wait” strategy of rectal cancer in complete remission after neoadjuvant chemoradiotherapy, and use esophagectomy as a salvage method for local recurrence? Multiple retrospective studies have demonstrated that among good responders after neoadjuvant therapy, active surveillance of patients who refused esophagectomy or were ultimately deemed unsuitable for surgery had comparable survival rates to those who underwent surgery ( 173 178 ). In the ongoing prospective SANO trial and ESOSTRATE trial, patients with a clinical response assessment of cCR after standard neoadjuvant chemoradiotherapy will be randomly assigned to either the active surveillance group or the immediate surgery group, comparing survival and quality of life for both groups ( 179 181 ).…”
Section: Discussion: Current Progress and Future Directionmentioning
confidence: 99%
“…Can esophageal cancer learn from the “watch and wait” strategy of rectal cancer in complete remission after neoadjuvant chemoradiotherapy, and use esophagectomy as a salvage method for local recurrence? Multiple retrospective studies have demonstrated that among good responders after neoadjuvant therapy, active surveillance of patients who refused esophagectomy or were ultimately deemed unsuitable for surgery had comparable survival rates to those who underwent surgery ( 173 178 ). In the ongoing prospective SANO trial and ESOSTRATE trial, patients with a clinical response assessment of cCR after standard neoadjuvant chemoradiotherapy will be randomly assigned to either the active surveillance group or the immediate surgery group, comparing survival and quality of life for both groups ( 179 181 ).…”
Section: Discussion: Current Progress and Future Directionmentioning
confidence: 99%
“… 13 , 14 As such, there is growing interest in the use of organ preservation using upfront CRT followed by surveillance and salvage procedures as a means to minimising treatment-related morbidity; with at least three randomised controlled trials planned within this space. 15 , 16 However, the effectiveness of these approaches is contingent on the timely identification of residual and recurrent disease in order to permit salvage resection or reirradiation through a brachytherapy boost or external beam proton therapy. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, the overall role of the primary non-surgical management of oesophageal cancer also remains uncertain and requires further investigation within the phase 3 trial setting. 15 Further work is also required to optimise the use of laboratory biomarkers, clinical factors and the Cytosponge to identify patients who require or who should endoscopic assessment. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that around 20%–40% of patients treated with nCRT would achieve a pCR, which has been demonstrated to be associated with improved recurrence‐free survival (RFS) and overall survival (OS) 5,6 . A meta‐analysis confirmed that OS was comparable in patients with clinically complete response (cCR) after chemoradiotherapy undergoing active surveillance or standard esophagectomy 7 . If pCR could be predicted with high accuracy, surgery could potentially be utilized as a salvage procedure instead of a planned procedure 8 .…”
Section: Introductionmentioning
confidence: 99%